Influenza among the elderly in the Americas: A consensus statement - Rüttimann, Ricardo W.; Bonvehí, Pablo E.; Vilar-Compte, Diana; Isturiz, Raúl E.; Labarca, Jaime A.; Vidal, Edison Iglesias de Oliveira [UNESP] (My University, 2013)
Influenza exacts a heavy burden on the elderly, a segment of the population that is estimated to experience rapid growth in the near future. In the past decade most developed and several developing countries have recommended influenza vaccination for those > 65 years of age. The World Health Organization (WHO) set a goal of 75% influenza vaccination coverage among the elderly by 2010, but it was not achieved. In 2011, the Technical Advisory Group at the Pan American Health Organization, Regional Office of WHO for the Americas, reiterated the influenza vaccine recommendation for older adults. Relatively little information has been compiled on the immunological aspect of aging or on reducing its impact, information particularly relevant for clinicians and gerontologist with firsthand experience confronting its effects. To fill this data gap, in 2012 the Americas Health Foundation (Washington, D.C., United States) and the nonprofit, Fighting Infectious Diseases in Emerging Countries (Miami, Florida, United States), convened a panel of Latin American clinicians and gerontologists with expertise in influenza to discuss key issues and develop a consensus statement. The major recommendations were to improve influenza surveillance throughout Latin America so that its impact can be quantified; and to conduct laboratory confirmation of influenza for all patients who have flu-like symptoms and are frail, immunosuppressed, have comorbidities, are respiratory compromised, or have been admitted to a hospital. The panel also noted that: since evidence for antivirals in the elderly is unclear, their use should be handled on a case-by-case basis; despite decreased immunological response, influenza vaccination in older adults is still crucial; indirect immunization strategies should be encouraged; and traditional infection control measures are essential in long-term care facilities.
Keywords: 80 and over; Aged; Consensus development conferences as topic; Health of the elderly; Human; Immunization; Influenza; Influenza vaccines; Latin America; adult; disease control; disease prevalence; elderly care; elderly population; estimation method; infectious disease; influenza; information management; symptom; Florida [United States]; Miami; United States